Interpretation and Implementation of UNESCO’s ‘Declaration on Bioethics and Human Rights’ - Todorovska, Marija (University of Rijeka, Croatia, 2010)
The beginning of the 21 century imposes the need of synchronising the practical and the academic approach in the interpretation of bioethical problems and the implications of their solving. Some of the goals of the Declaration are the education of health-care professionals, the creation the infrastructure necessary for biomedical research and the education of the scientists involved in it, and the foundation of ethical committees. Th e Declaration provides with a legal and political guidelines, whereas for a full justification and development of the its general idea, a philosophical (epistemological and axiological) background as a sustaining meta-theory is much needed. Th e pluriperspectivity and the multidisciplinarity of the integrative bioethics construct a perfect methodological framework for a theoretical justification and a in-depth explication of the most important and the subtlest recommendations of the Declaration.
Keywords: declaration, meta-theory, pluriperspectivity, multidisciplinarity